Historical inference based on semi-supervised learning - Lee, Dong gi; Lee, Sangkuk; Kim, Myungjun; Shin, Hyunjung (Expert Systems with Applications, 2018)
In the past, most historical research has been manually carried out by exploring historical facts reading between the lines of documents. Nowadays, historical big data has become electronically available and advances in machine learning techniques allow us to analyze the vast amount of historical data. From a historical perspective, making inferences about political stances of historical figures is important for grasping historical rivalries and power structures of an era. Thus, in this paper, we propose an approach to the systematic inference of power mechanisms based on a human network constructed from historical data. In this network, humans are linked according to the degree of kinship using genealogy records, and identified by political stances on agendas recorded in the annals of a dynasty as a political force. And then, a machine learning algorithm, semi-supervised learning, classifies humans who cannot identify political stances as political forces that reflect the links of the networks. The data consist of the genealogy of the Andong Gwon clan, a record of family relations of 10,243 people from the 10th to 15th century Korea, and the Annals of the Joseon Dynasty, a historical volume that describes historical facts of the Joseon Dynasty for 472 years and is composed of 1894 fascicles and 888 books. From the data, we construct a human network based on a historically meaningful period (1443–1488), and classify people into two political forces using the proposed method. We suggest that this machine learning approach to historical study could be utilized as a potent reference tool devoid of the subjectivism of human experts in the field of history.
Keywords: Annals of the Joseon Dynasty; Genealogy; Historical perspective; Historical research; Machine learning approaches; Machine learning techniques; Power structures; Semi- supervised learning; Genealogy; Historical big data; Machine learning; Semi-supervised learning